2016
DOI: 10.3846/bjrbe.2016.09
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on using basalt fiber filaments in the construction and rehabilitation of highway pavements and airport runways

Abstract: With the ageing transportation infrastructure, many transportation agencies across the world are focussing on rehabilitating and improving existing pavements. This means more roadwork on pavements open to vehicular traffic. Considering the rapid increase in both traffic volume and intensity in recent years, the work conditions on pavements have become difficult. Thus, there is an important need to design and construct long-lasting pavements that possess high durability, appropriate roughness or smoothness, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Thus, by plunging into the dam of additional volumes of piles will be compensated all strain elongation until the moment of their complete damping that will completely exclude the possibility of appearance the hazardous cracks for the dam [22][23][24][25][26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by plunging into the dam of additional volumes of piles will be compensated all strain elongation until the moment of their complete damping that will completely exclude the possibility of appearance the hazardous cracks for the dam [22][23][24][25][26].…”
Section: Methodsmentioning
confidence: 99%
“…Where ‫ݎ‬ -sectional radius of the pile, ‫ܧ‬ ୡ୭୫ and ߤ -modulus of deformation compression and coefficient Poisson for soil around the pile, ‫ݎ‬ -the distance from the point considered in the soil to the pile axis, ܴ ୢ -the radius of the deformed zone of soil around the pile at her pile, taken equal to half the maximum distance between adjacent piles [25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that organic fibers have some disadvantages such as low strength and modulus, poor resistance to high and low temperatures, and high water absorption. Besides, they also present degradation, oxidation reaction, and curling problems during mixing and paving process [7,11,12]. e chopped basalt fiber is made of natural basalt rocks, which are broken and thrown into a melting furnace.…”
Section: Introductionmentioning
confidence: 99%
“…They enable us to verify the theoretical assumptions, as well as determining use factors which so affect the capacity of the construction they cannot be predicted theoretically. When observing a bridge structure, vertical displacements are very important because they have the biggest impact on the structure and its eventual deformation, while the horizontal displacements are tested especially in the case of rail lines and in more demanding engineering measurements of deformation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%